STUDY OF THE ANATOMIC STRUCTURE OF THE CHONDRILLA JUNCEA L. HERB - V. N. Bubenchikova; V. N. Levchenko (Фармация и фармакология (Пятигорск))
The article presents the results of the anatomical structure of the aerial part of Chondrilla juncea L. The study has found that the stem has a beam-type structure, pubescent with simple multicellular fuzz, which cells are filled with brown contents. We have noted the presence of leaf epidermis cells with thick walls. While studying the inflorescence we have determined the character of involucre leaflets pubescence and semiflorets with simple one cell fuzz with tapered pointed top and spread base, also involucre leaflets have often twisted pluricellular thin-walled simple fuzz with matching walls, and ovary pubescence with simple thin-walled multiple-row fuzz, pointed up and slightly deflected. Chyles presence is one of the diagnostic features of Chondrilla juncea L. herb.